Get Answers to all your Questions

header-bg qa

Need solution for RD Sharma Maths Class 12 Chapter 10 Differentiation Excercise 10.7 Question 26

Answers (1)


            \frac{d y}{d x}=t


            Use quotient rule and   \frac{d y}{d x}=\frac{\frac{d y}{d \theta}}{\frac{d x}{d \theta}}


            \begin{aligned} &x=\frac{1+\log t}{t^{2}} \\ &y=\frac{3+2 \log t}{t} \end{aligned}


x=\frac{1+\log t}{t^{2}} \\

\frac{d x}{d t}=\frac{d\left(\frac{1+\log t}{t^{2}}\right)}{d t} \\

\begin{aligned} &=\frac{t^{2} \frac{d(1+\log t)}{d t}-(1+\log t) \frac{d t^{2}}{d t}}{\left(t^{2}\right)^{2}} \end{aligned}                                                                            [Using quotient rule]

\frac{d x}{d t}=\frac{t\left[\frac{d(1)}{d t}+\frac{d \log t}{d t}\right]-(1+\log t) \cdot 2 t}{t^{4}} \\

=\frac{t^{2}\left(0+\frac{1}{t}\right)-2 t-2 t \log t}{t^{4}} \\

=\frac{t-2 t-2 t \log t}{t^{4}} \\

\begin{aligned} & &=\frac{-t-2 t \log t}{t^{4}} \end{aligned}

\frac{d x}{d t}=\frac{-(1+2 \log t)}{t^{3}} \\                                                                                                                                        (1)

\begin{aligned} & &y=\frac{3+2 \log t}{t} \end{aligned}

\frac{d y}{d t}=\frac{d\left(\frac{3+2 \log t}{t}\right)}{d t} \\

\begin{aligned} &=\frac{t \cdot \frac{d(3+2 \log t)}{d t}-(3+2 \log t) \frac{d t}{d t}}{t^{2}} \end{aligned}                                                                      [Using quotient rule]

=\frac{t\left(\frac{2}{t}\right)-(3+2 \log t)}{t^{2}} \\

\frac{d y}{d t}=\frac{2-3-2 \log t}{t^{2}} \\

=\frac{-1-2 \log t}{t^{2}} \\

\begin{aligned} & &\frac{d y}{d t}=\frac{-(1+2 \log t)}{t^{2}} \end{aligned}                                                                                                                                        (2)

\frac{d y}{d x}=\frac{\frac{d y}{d t}}{\frac{d x}{d t}}

So put \frac{d x}{d t} \text { and } \frac{d y}{d t}   from equation (1) and (2) respectively

\frac{d y}{d x}=\frac{\frac{-(1+2 \log t)}{t^{2}}}{\frac{-(1+2 \log t)}{t^{3}}}=\frac{-(1+2 \log t) \times t^{3}}{-(1+2 \log t) \times t^{2}}

\\ =\frac{t^{3}}{t^{2}}=t \\

\begin{aligned} & &\frac{d y}{d x}=t \end{aligned}


Posted by


View full answer

Crack CUET with india's "Best Teachers"

  • HD Video Lectures
  • Unlimited Mock Tests
  • Faculty Support